A review of cardiac rehabilitation benefits on physiological aspects in patients with cardiovascular disease - Fatemeh Esteki Ghashghaei; Masoumeh Sadeghi; Safura Yazdekhasti (Vesnu Publications, 2012)
Introduction: Nowadays cardiovascular disease is a major problem in the world which is known as a leading cause of morbidity and morality. Since, physical activity and exercise training have beneficial role in prevention and treatment of cardiovascular disease; so, cardiac rehabilitation units on the basis of exercise training were established in 1960. Therefore, with attention to scientific evidence, researchers want to review the effects of various exercise training during cardiac rehabilitation program to facilitate return to an active lifestyle in patients with coronary heart disease. Materials and Methods: Comprehensive cardiac rehabilitation consists of medical measurement, exercise prescription, cardiac risk factors modification, education and consultation with the purpose of primary and secondary prevention. Conclusion: These interventions have been designed to limit the progression of cardiac diseases and their related symptoms, to improve psychological status, to increase functional capacity and above all, to reduce cardiovascular mortality. Also, exercise training which has been identified as an integral component of cardiac rehabilitation has useful effects on cardiac disease by decreasing cardiac work load, reduction oxygen in use, improvement myocardial function and endothelial vessels flexibility and increasing maximum oxygen consumption. Keywords: Cardiac rehabilitation, Cardiovascular disease, Exercise training